Quantification of insecticides in commercial seafood sold in East Asian markets: risk assessment for consumers - Ivorra, Lucia; Cardoso, Patricia G.; Chan, Shek Kiu; Cruzeiro, Catarina; Tagulao, Karen (Environmental Science and Pollution Research, 2023)
The extraction of 21 insecticides and 5 metabolites was performed using an optimized and validated QuEChERS protocol that was further used for the quantification (GC–MS/MS) in several seafood matrices (crustaceans, bivalves, and fish-mudskippers). Seven species, acquired from Hong Kong and Macao wet markets (a region so far poorly monitored), were selected based on their commercial importance in the Indo-Pacific region, market abundance, and affordable price. Among them, mussels from Hong Kong, together with mudskippers from Macao, presented the highest insecticide concentrations (median values of 30.33 and 23.90 ng/g WW, respectively). Residual levels of fenobucarb, DDTs, HCHs, and heptachlors were above the established threshold (10 ng/g WW) for human consumption according to the European and Chinese legislations: for example, in fish-mudskippers, DDTs, fenobucarb, and heptachlors (5-, 20- and tenfold, respectively), and in bivalves, HCHs (fourfold) had higher levels than the threshold. Risk assessment revealed potential human health effects (e.g., neurotoxicity), especially through fish and bivalve consumption (non-carcinogenic risk; ΣHQLT > 1), and a potential concern of lifetime cancer risk development through the consumption of fish, bivalves, and crustaceans collected from these markets (carcinogenic risk; ΣTCR > 10–4). Since these results indicate polluted regions, where the seafood is collected/produced, a strict monitoring framework should be implemented in those areas to improve food quality and safety of seafood products.
Keywords: Bivalves; Crustaceans; Health risk assessment; Mudskippers; Organochlorine pesticides

Can mangroves work as an effective phytoremediation tool for pesticide contamination? An interlinked analysis between surface water, sediments and biota - Ivorra, Lucia; Cardoso, Patricia G.; Chan, Shek Kiu; Cruzeiro, Catarina; Tagulao, Karen Arano (Journal of Cleaner Production, 2021)
Mangroves are a unique group of plants growing along tropical and sub-tropical coastlines, with the ability to remove several types of contaminants such as heavy metals and other persistent organic compounds in coastal waters. However, little attention has been given to the possible role of mangroves in the removal of organochlorinated pesticides (OCPs) from the environment. Used worldwide, these pesticides were banned in the late 80s, withal they can still be quantified in aquatic environments due to their high stability. Moreover, as persistent and lipophilic compounds, OCPs are known for their tendency to bioaccumulate and biomagnify through the food chain, affecting local ecosystems, and potentially human health. This work aimed to investigate the potential benefits of mangrove ecosystems as OCP phytoremediators. For this purpose, a total of seventy-three articles from non-mangrove and mangrove areas around the world were gathered, integrated and re-analysed as a whole. These data include information from four different matrices (water, sediment, benthic fauna and mangrove plants). A common trend of less pesticide contamination in mangrove areas was observed for all the selected matrices. As a complement, average concentrations were discussed considering International Directives, such as the European legislation 2013/39/EU for water policy and the Dutch List together with the International Sediment Quality Guideline, for sediments. Additionally, theoretical risk assessments were also included. Since information regarding OCPs in mangroves ecosystem is very scarce compared to non-mangrove areas, this review provides valuable insights regarding these environments, and the importance of preserving them as a relevant remediation unit.
Keywords: Benthic fauna; Intertidal environments; Organochlorinated pesticides; Persistent organic compounds; Toxicological assessment

Uptake and depuration kinetics of dicofol metabolite 4,4′-dichlorobenzophenone, in the edible Asiatic clam Meretrix meretrix - Ivorra, Lucia; Cruzeiro, Catarina; Chan, Shek Kiu; Tagulao, Karen Araño; Cardoso, Patricia G. (Chemosphere, 2019)
Uptake and depuration kinetics of 4,4′-dichlorobenzophenone (main metabolite of dicofol) in the edible clam Meretrix meretrix were evaluated through a mesocosm experiment. M. meretrix was exposed to different dicofol concentrations (environmental concentration, D1 = 50 ng/L; supra-environmental concentration, D2 = 500 ng/L) for 15 days, followed by the same depuration period. To accomplish this goal, an analytical method was successfully optimized for 4,4′-DCBP using QuEChERS as extraction method with a range of concentrations 0.3–76.8 ng/g ww quantified by gas chromatography coupled to tandem mass spectrometry. Our results demonstrated different kinetics of accumulation depending on the two dicofol treatments. For D1, the uptake kinetic was best fitted using a plateau followed by one phase association kinetic model, while for D2 a one phase association kinetic model suited better. Similar bioconcentration factors were obtained for both concentrations but only animals exposed to D2, showed 4,4′-DCBP levels above the limits of quantification after 24 h exposure. These animals also showed lower uptake rate (ku) than organisms exposed to D1. During the depuration period, only organisms exposed to D1 successfully depurated after 24 h. On the other hand, although animals exposed to D2 presented higher elimination factor, they did not reach the original levels after depuration. Moreover, values detected in these clams were higher than the Maximum Residue Level (10 ng/g) established by the European legislation. This indicates that longer periods of depuration time than the ones used in this study, may be needed in order to reach safe levels for human consumption. This work also demonstrated that studies on metabolite kinetics during uptake/depuration experiments, could be a new alternative to understand the impact and metabolism of pesticides in the marine environment.
Keywords: Bivalves; GC-MS/MS; Organochlorine pesticides; QuEChERS bioconcentration; Seafood

Environmental characterization of 4,4′-dichlorobenzophenone in surface waters from Macao and Hong Kong coastal areas (Pearl River Delta) and its toxicity on two biological models: Artemia salina and Daphnia magna - Ivorra, Lucia; Cardoso, Patricia G.; Chan, Shek Kiu; Tagulao, Karen; Cruzeiro, Catarina (Ecotoxicology and Environmental Safety, 2019)

The role of mangroves on the bioaccumulation and citogenotoxic effects of metals and pesticides on the food web of a sub-tropical coastal system - Chan, Shek Kiu; Tagulao, Karen (University of Saint Joseph, 2018)

Use of stable isotopes to understand food webs in Macao wetlands - Chen, Qian; Liu, Yang; Ho, Wei-Tim; Chan, Shek Kiu; Li, Qiu-hua; Huang, Jian-Rong (Wetlands Ecology and Management, 2017)
In this study, components of the food-web in Macao wetlands were quantified using stable isotope ratio techniques based on carbon and nitrogen values. The δ13C and δ15N values of particulate organic matter (δ13CPOM and δ15NPOM, respectively) ranged from −30.64 ± 1.0 to −28.1 ± 0.7 ‰, and from −1.11 ± 0.8 to 3.98 ± 0.7 ‰, respectively. The δ13C values of consumer species ranged from −33.94 to −16.92 ‰, showing a wide range from lower values in a freshwater lake and inner bay to higher values in a mangrove forest. The distinct dietary habits of consumer species and the location-specific food source composition were the main factors affecting the δ13C values. The consumer 15N-isotope enrichment values suggested that there were three trophic levels; primary, secondary, and tertiary. The primary consumer trophic level was represented by freshwater herbivorous gastropods, filter-feeding bivalves, and plankton-feeding fish, with a mean δ15N value of 5.052 ‰. The secondary consumer level included four deposit-feeding fish species distributed in Fai Chi Kei Bay and deposit-feeding gastropods in the Lotus Flower Bridge flat, with a mean δ15N value of 6.794 ‰. The tertiary consumers group consisted of four crab species, one shrimp species, and four fish species in the Lotus Flower Bridge Flat, with a mean δ15N value of 13.473 ‰. Their diet mainly comprised organic debris, bottom fauna, and rotten animal tissues. This study confirms the applicability of the isotopic approach in food web studies.

The role of mangroves on the bioaccumulation and citogenotoxic effects of metals and pesticides on the food web of a tropical coastal system - Chan, Shek Kiu; Tagulao, Karen (University of Saint Joseph, 2016)